2012
DOI: 10.1155/2012/479016
|View full text |Cite
|
Sign up to set email alerts
|

Red Ginseng Extract Attenuates Kainate-Induced Excitotoxicity by Antioxidative Effects

Abstract: This study investigated the neuroprotective activity of red ginseng extract (RGE, Panax ginseng, C. A. Meyer) against kainic acid- (KA-) induced excitotoxicity in vitro and in vivo. In hippocampal cells, RGE inhibited KA-induced excitotoxicity in a dose-dependent manner as measured by the MTT assay. To study the possible mechanisms of the RGE-mediated neuroprotective effect against KA-induced cytotoxicity, we examined the levels of intracellular reactive oxygen species (ROS) and [Ca2+]i in cultured hippocampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Our study also showed that, after arsenic exposure, ROS-induced oxidative damage increased MDA and GSSH production in the kidney, which is consistent with the results of previous studies [18]. However, the intrinsic antioxidant defenses of cells play a crucial role in the elimination of free radicals, including enzymatic antioxidant and non-enzymatic systems [19]. Both SOD and GPx are important endogenous antioxidant enzymes that destroyed the superoxide anion radical through dismutation and generated H2O2.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also showed that, after arsenic exposure, ROS-induced oxidative damage increased MDA and GSSH production in the kidney, which is consistent with the results of previous studies [18]. However, the intrinsic antioxidant defenses of cells play a crucial role in the elimination of free radicals, including enzymatic antioxidant and non-enzymatic systems [19]. Both SOD and GPx are important endogenous antioxidant enzymes that destroyed the superoxide anion radical through dismutation and generated H2O2.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, it has been shown that KRG increased sperm concentration, motility and morphology under different experimental conditions in 2, 3, 7, 8‐tetrachlorodaibenzo‐p‐dioxin‐exposed rats (Park et al., ), aged rats (Hwang, Sohn & Wee, ), intact rats (Park et al., ) and dioxin‐exposed guinea pigs (Hwang, Kim, Wee, Choi & Kim, ). The protective effect of KRG on sperm parameters could most likely be attributed to its antioxidant effects, scavenging ROS and enhancement of the antioxidative defence system to attenuate free radical‐induced damage that resulted from UPEC (Han et al., ; Jang, Lee, Shin, Lee & Ernst, ). Park et al.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] In addition, KRG extract has been shown to protect SK-N-SH cells 19) and hippocampal cells 18) against H 2 O 2 -induced oxidative stress and kainateinduced neurotoxicity, respectively, implying its additional beneficial actions in the CNS. We observed in this study that KRG extract inhibited glutamate-or NMDA-induced excitotoxicity as well as A β -induced neurotoxicity in primary cultured rat cortical cells.…”
Section: Discussionmentioning
confidence: 99%